Efficient optical fiber coupling to whispering gallery modes of optically manipulated emulsion microdroplets - (:unkn) unknown (Electromagnetics Academy, 2015)
We demonstrate efficient coupling to the optical whispering gallery modes of a spherical resonator consisting of a liquid droplet embedded in another liquid medium. Whispering gallery mode particle sensing experiment is commonly performed with solid resonators, whereby the sensing volume is limited to the weak evanescent tail of the mode near the resonator surface. In this work, we demonstrate efficient coupling to the optical whispering gallery modes by introducing a portable, all liquid emulsion microdroplet resonator held in a single beam optical trap. We have observed coupling to the fundamental whispering gallery modes of 10 to 60 nm diameter emulsion droplets at 1550 nm. The experimental challenges towards making, stabilizing and coupling to the droplet resonators are also addressed in this paper.